Desenvolvimento de eletrodo de filme de bismuto depositado sobre cobre para aplicações eletroanalíticas - Nunes, Luiza Maria da Silva (2007)
On this work is described the development of bismuth film electrode deposited over copper substrate for electroanalytical applications. The bismuth film electrode was deposited ex situ over a copper substrate. The electrodeposition of Bi was carried out applying a constant potential of -150 mV during 300 s. The plating solution was composed by 0.02 mol L-1 Bi(NO)3 in 1.0 mol L-1 hydrochloride acid with or not 0.08 mol L-1 sodium citrate, the electrodes obtained from these solutions were nominated Bi-Cit008 and Bi-HCl, respectively. The bismuth film characterization was carried out by Field Emission Gun Scanning Electron Microscopy (FEG-SEM), Scanning Electron Microscopy with Energy Dispersive X-ray analysis (MEV-EDX) and X-Ray Diffraction analysis. The FEG-SEM and MEV-EDX analysis of bismuth film showed that the morphology of the deposits were strongly dependent of the plating solution composition. X-Ray diffraction analysis showed a single rhombohedral and cubic phase for the two bismuth film electrodes analyzed. The Bi-HCl and Bi-Cit008 electrodes showed a good cathodic potential window from -300 mV to -1200 mV. Both electrodes, exhibited a good analytical response for cadmium and lead by means of square wave anodic stripping voltammetry technique. For the lead determination, Bi-HCl and Bi-Cit008 electrodes showed a detection limit of 2.8 x 10-8 mol L-1 and 2.5 x 10-8 mol L-1, respectively in a concentration range from 9.6 x 10-6 to 5.7 x 10-5 mol L-1. For the cadmium determination, Bi-HCl and Bi-Cit008 electrodes presented a detection limit of 1.1 x 10-6 mol L-1 and 6.3 x 10-8 mol L-1, respectively in the concentration range from 1.7 x 10-5 to 12.3 x 10-5 mol L-1. Both electrodes, presented analytical response with good resolution without baseline dislocation, therefore, Bi-Cit008 had best analytical performance.